Play, expression and collectivity: a joint children's stage creation experience. (The Voz a Vos Bulletin, 2025)
This research aims to create a children's theater play based on emotions, developed within a theatrical creation laboratory with children aged 9 to 12 from the institutional theater group at Instituto Diversificado Albert Einstein, located in Mosquera, Colombia. The study seeks to understand how the process of creating and performing theater, centered on emotional exploration, contributes to the development of creativity, imagination, and expressive skills in a school context. The project is structured in progressive stages, beginning with a sensitization phase that includes literary and audiovisual references (The Color Monster, Inside Out, and Jack and the Cuckoo-Clock Heart), followed by dramatic play activities guided by open-ended questions that lead participants to create characters and situations. These creations form the basis of a collective dramaturgical proposal, culminating in a public performance for the school community. The research adopts a practice-as-research (research-creation) methodology, which recognizes artistic creation as a valid form of situated and sensitive knowledge production. Data collection is carried out through reflective field journals, audiovisual records, theatrical exercises, and group discussions, allowing an experiential understanding of the creative process.
Keywords: Dramatic play; Collective creation; Theatrical performance